2003
DOI: 10.1093/toxsci/kfg107
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Dioxins, Furans, and Non-ortho PCBs Based upon Consensus Toxic Equivalency Factors Produces Dioxin-Like Reproductive Effects

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD; dioxin) and related polyhalogenated aromatic hydrocarbons (PHAHs) alter the reproductive development of laboratory animals. Therefore, we exposed animals to a mixture of dioxins, furans, and polychlorinated biphenyls (PCBs) that included TCDD, 1,2,3,7,8-pentachlorodibenzo-p-dioxin (PeCDD), 2,3,7,8-tetrachlorodibenzofuran (TCDF), 1,2,3,7,8-pentachlorodibenzofuran (1-PeCDF), 2,3,4,7,8-pentachlorodibenzofuran (4-PeCDF), octachlorodibenzofuran (OCDF), 3,3',4,4'-tetrachlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 45 publications
5
21
0
Order By: Relevance
“…In utero and lactational TCDD exposure in rodents has been associated with delays in pubertal development [e.g., delayed vaginal opening, altered vaginal estrous cyclicity (Gray and Ostby 1995; Wolf et al 1999)] and effects on ovarian function (Gray and Ostby 1995; Heimler et al 1998), even at doses below those that induce overt maternal toxicity. A similar spectrum of reproductive alterations has been associated in rodents exposed in utero to other dioxin-like compounds, including PCDDs, PCDFs, and PCBs (Faqi et al 1998; Hamm et al 2003; Muto et al 2003; Sager and Girard 1994). …”
mentioning
confidence: 57%
“…In utero and lactational TCDD exposure in rodents has been associated with delays in pubertal development [e.g., delayed vaginal opening, altered vaginal estrous cyclicity (Gray and Ostby 1995; Wolf et al 1999)] and effects on ovarian function (Gray and Ostby 1995; Heimler et al 1998), even at doses below those that induce overt maternal toxicity. A similar spectrum of reproductive alterations has been associated in rodents exposed in utero to other dioxin-like compounds, including PCDDs, PCDFs, and PCBs (Faqi et al 1998; Hamm et al 2003; Muto et al 2003; Sager and Girard 1994). …”
mentioning
confidence: 57%
“…These investigators found that, while their toxicant mixture produced similar effects as that of TCDD alone, a higher dose of the mixture was required due to TCDD's greater efficiency of transfer to the offspring. Although continued assessment of toxicant mixtures is highly desirable, there is still much value in studies assessing the impact of individual toxicants, particularly TCDD, because this highly toxic contaminant is so easily transferred from the maternal to the fetal and neonatal compartment (21,22).…”
Section: Environmental Tcdd Exposurementioning
confidence: 99%
“…Moreover, the risk associated with a mixture of DLCs may be estimated based on the effects of 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD), the most potent member of this class of compounds, and using a dose metric that is based on the summation of the mass of each compound in the mixture after adjustment for its potency relative to that of TCDD. This concept of potency-adjusted dose additivity has been evaluated for a number of end points (DeVito et al 1997; Hamm et al 2003; Toyoshiba et al 2004) but has never been evaluated for cancer risk from chronic/lifetime exposure. Given that assessments of human cancer risk are based in part on data obtained from rodent carcinogenicity studies, it is important and appropriate to assess whether the concept of dose additivity is valid for the carcinogenicity of a mixture of DLCs within the context of a rodent cancer bioassay.…”
mentioning
confidence: 99%